2022
DOI: 10.1126/sciadv.abm7723
|View full text |Cite
|
Sign up to set email alerts
|

Mating-driven variability in olfactory local interneuron wiring

Abstract: Variations in neuronal connectivity occur widely in nervous systems from invertebrates to mammals. Yet, it is unclear how neuronal variability originates, to what extent and at what time scales it exists, and what functional consequences it might carry. To assess inter- and intraindividual neuronal variability, it would be ideal to analyze the same identified neuron across different brain hemispheres and individuals. Here, using genetic labeling and electron microscopy connectomics, we show that an identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Additionally, previous work has shown unique roles for subpopulations of LNs (Chou et al, 2022;Huang et al, 2010;Liu and Wilson, 2013;Sizemore et al, 2022;Suzuki et al, 2020).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, previous work has shown unique roles for subpopulations of LNs (Chou et al, 2022;Huang et al, 2010;Liu and Wilson, 2013;Sizemore et al, 2022;Suzuki et al, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…Physiologic characterization of LNs has revealed distinctions ( Chou et al, 2010 ; Seki et al, 2010 ) and some classes of these LNs have been probed for morphology. Additionally, previous work has shown unique roles for subpopulations of LNs ( Huang et al, 2010 ; W.W. Liu and Wilson, 2013 ; Suzuki et al, 2020 ; Chou et al, 2022 ; Sizemore et al, 2022 ). However, correlating LN physiology with morphology remains difficult.…”
Section: Introductionmentioning
confidence: 98%
“…On the other, the truncated and large number of new EM morphologies, the difficulty in assigning cell types and the lack of comprehensive inter-and intra-individual comparisons for both sexes. Common to both is the experience-dependent or -independent morphological and connectivity variability [17,32,78]. This process of mapping cell types also leads to the identification of driver lines [28,29] that can be used for behavioural assays and the increase in the availability of sparsely labelled lines [79] is facilitating this process.…”
Section: Challengesmentioning
confidence: 99%
“…10.3389/fncir. 2022.949781 Strikingly, a recent study revealed that mating experience also modulates the wiring of olfactory neurons in the female brain (Chou et al, 2022). A set of inhibitory olfactory local neurons ("TC-LN") exhibit specific and significantly increased innervation of the VL2a glomerulus, possibly contributing to feeding behaviors in post-mated females.…”
Section: Social Experience and Mating Behaviors In Fliesmentioning
confidence: 99%